Identification Of Types Of Fungus Candida Albicans In The Urine Of Pregnant Women In The Thirty Trimester At RSI Surabaya Jemursari - Iis Rofiatul Ana; Pestariati, Pestariati; Christ Kartika Rahayuningsih (Sean Institute, 2024)
Candidiasis is an infection caused by the fungus Candida albicans, especially in pregnant women in the third trimester. This infection, known as Vulvovaginal Candidiasis (VVC), occurs due to the growth of Candida on the vaginal wall. Increased estrogen hormone during pregnancy increases glycogen levels in the vagina, which is a source of carbon for Candida albicans. This study aims to identify the presence of Candida albicans in the urine of pregnant women in the third trimester at RSI Jemursari Surabaya. The study was descriptive qualitative involving 18 samples of pregnant women who experienced symptoms of itching in the vaginal area and vaginal discharge. The results showed that 5 pregnant women (27.8%) were positive for Candida albicans infection, while 13 pregnant women (72.2%) were negative. Examination was carried out macroscopically with Sabouraud Dextrose Agar (SDA) media, followed by microscopic examination using Lactophenol Cotton Blue (LPCB) staining, and a specific germ tube test. This study concluded that 27.8% of pregnant women in the third trimester were infected with Candida albicans from the identification results in urine samples.